Avaliação morfológica do oviduto e qualidade de ovos de poedeiras comerciais (Gallus gallus) em diferentes fases de produção - TAKATA, Fátima Naomi (2006)
The laying hens available currently is submit genetics modified for produce greatest egg an low cost. The important fact for continuation this evolution is knowledge the cell oviduct (“egg factory”). In laying (Gallus gallus) the oviduct is describe with muscular tube winding, its length esteemed between 14 and 19 cm in outside the ovoposition and 42 and 86 during ovoposition. Opening next ovary and end in cloak, compose whit six region, the fimbrias, infundibulun, magnum, isthmus, shell gland and vagin. The egg quail is check for describe a different in production fresh egg, for genetics characteristics, diet and environmental factors. This works study a laying hens oviduct morphology associate in productions rate and egg quail. We available 2456 laying. For morphology studding using 80 hens divide in eight groups. The collect fact in different stage the production, between 20 and 60 age week. The material are processed for habitual techniques in histological laboratories. The oviduct epithelial morphology (in magnum, isthmus and shell gland) don`t variable with increase the age and productions, however we observe increase in glands at mucous. We are using 30 eggs for group. The egg quail observe a positive correlation between age with egg mass, egg white and yolk. The shell mass dont´t significant correlation with egg mass, this fact explained low quail and increased the loss in relation to broken to egg. Dont´t observe changes in physiology compositions in the oviduct with advance to age. This fact a indicative a most attention for nutritional requirement add up to management and appropriate environment for rear this poultry.